Long‐Term Variations of the Geomagnetic Activity: A Comparison Between the Strong and Weak Solar Activity Cycles and Implications for the Space Climate. Issue 4 (25th March 2021) - Hajra, Rajkumar; Marques de Souza Franco, Adriane; Echer, Ezequiel; José Alves Bolzan, Mauricio
Abstract: We study the long‐term variations of geomagnetic activity using more than five solar cycles of geomagnetic and solar wind observations. From the Dst index variation, 1523 geomagnetic storms were identified during January 1957 through December 2019, and 145 high‐intensity long‐duration continuous auroral electrojet (AE) activity (HILDCAA) events were identified using the AE index from January 1975 through December 2017. Among the storms, ∼3/4th were moderate (−50 nT ≥ Dst > −100 nT), and only ∼1/4th were stronger in intensity (Dst ≤ −100 nT). Cross‐correlation analysis reveals a strong correlation ( r = 0.58−0.78) between the magnetic storms and the F10.7 solar flux at 0−1‐year time lag and a weaker correlation ( r = 0.59) between HILDCAAs and F10.7 at a ∼3‐year lag. This result is consistent with the magnetic storm occurrence rate centered around the solar cycle maximum with a secondary peak after the maximum, and HILDCAAs peaking around the descending phase. Wavelet analysis reveals a dominating ∼10–11‐year periodicity in the number of geomagnetic storms and HILDCAAs, geomagnetic activity indices, solar wind, and interplanetary parameters. The periodicity is attributed to the solar activity cycle variation. Solar wind speed induces additional longer (∼15−16 years) and shorter (∼3−5 years) scale variations in geomagnetic activity. Solar cycles 20 and 24 are found to be significantly weaker compared to the cycles 19, 21, 22, and 23 in solar flux, solar wind‐magnetosphere coupling, and resultant geomagnetic activity. If the decreasing trend of the solar and geomagnetic activities continues in cycle 25, this may have important implications for the space weather science and operations. Key Points: The long‐term variations in the geomagnetic activity and the solar wind‐magnetosphere coupling are studied The geomagnetic activities of different types exhibit varying solar cycle dependencies The weak solar cycles are associated with the reduced solar wind‐magnetosphere coupling and geomagnetic activity